2012
DOI: 10.1111/cas.12033
|View full text |Cite
|
Sign up to set email alerts
|

Implication of 14‐3‐3ε and 14‐3‐3θ/τ in proteasome inhibition‐induced apoptosis of glioma cells

Abstract: Proteasome inhibitors represent a novel class of anticancer agents that are used in the treatment of hematologic malignancies and various solid tumors. However, mechanisms underlying their anticancer actions were not fully understood. It has been reported that strong 14‐3‐3 protein expression is observed and associated with tumor genesis and progression of astrocytoma. In addition, global inhibition of 14‐3‐3 functions with a general 14‐3‐3 antagonist difopein induces apoptosis of human astrocytoma cells, vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…This finding can be explained by the functional role of 14-3-3θ. Specifically, 14-3-3θ binds to Bax and enhances Bax degradation to repress apoptosis and promote tumor cells proliferation [11, 16]. A recent study suggested that 70-75% of recurrent breast tumors have high expression of 14-3-3ζ, and primary tumors that had low levels of 14-3-3ζ expression had higher levels in the recurrence [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding can be explained by the functional role of 14-3-3θ. Specifically, 14-3-3θ binds to Bax and enhances Bax degradation to repress apoptosis and promote tumor cells proliferation [11, 16]. A recent study suggested that 70-75% of recurrent breast tumors have high expression of 14-3-3ζ, and primary tumors that had low levels of 14-3-3ζ expression had higher levels in the recurrence [17].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other 14-3-3 isoforms, few studies on 14-3-3θ have been conducted, and the studies that have evaluated the role of 14-3-3θ have all focused on cell survival and apoptosis [7, 8]. Deletion of 14-3-3θ in mice leads to embryonic lethality, and the cardiocytes of 14-3-3θ+/- mice are resistant to cardiomyocyte apoptosis [9].…”
Section: Introductionmentioning
confidence: 99%
“…More than 200 binding partners of the 14‐3‐3 protein have been reported, and the functions of the binding complex are widely involved in transcription, cell signalling, cytoskeletal organisation and cell apoptosis (Jin et al, ; Prasad et al, ). A previous study also demonstrated that downregulation of 14‐3‐3ε and its specific siRNAs suppressed cell viability and induced apoptosis (Yan et al, ). Thus, 14‐3‐3ε is the candidate gene for our subsequent study about apoptosis in germ cells.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, the upstream mechanism causing the 14‐3‐3ε downregulation in germ cells induced by varicocele is another focus of this study. Screening promoter regions of 14‐3‐3 isoforms demonstrated that the 14‐3‐3ε gene contains potential NF‐κB binding sequencing, and further investigation is essential to clarify this related item (Yan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, tumor tissues are dissociated into single cells by mechanical dissociation (e.g., meshing, trituration with a pipette/tip) [40][41][42] or by enzymatic dissociation [43][44][45] or a combination of both. Enzymes such as collagenase [41] , DNase [46] , trypsin [47] are commonly used for dissociating the cell-cell contacts and the extracellular matrix to generate single cell suspensions.…”
Section: Single-cell Isolation By Mechanical or Enzymatic Dissociationmentioning
confidence: 99%